STUDI KUALITATIF PEMAKNAAN APLIKATIF SHALAT SOSIAL - Mursidin Mursidin (Psympathic : Jurnal Ilmiah Psikologi, 2010)
Salat is as a medium of connection the communication between human and God. In implementation, salat taught many kinds of moral. The purpose of this research is get the clarification about salat and social piety. This research is as a qualitative research because the data of research is not a statistic data. The researcher finds the different view of salat. First doctrine of salat  has the certain meaning that related to morality. That is, if the doer of salat implements and experiences of the full salat the moral value has the functiom to form the good personality. Second the pure view based on fiqh limit of rules and ritual duty. According to this view, salat related to ritual duty. Salat doesn’t contain moral dimension because salat has the certain space in system of Islam doctrine that separated from system of salat doctrine.